News about Turkey in “Kazakh” and “Ak zhol” publications (Journal of history, 2022)
The content of the article in the heading “external communications” in the newspapers “Kazakh” and “Ak Zhol”, published in the early twentieth century in the national style, in the shortest possible time covers the political events of the last era of the Ottoman Empire to the Kazakh people.Since the first publication of the series “external messages” on the pages of the newspaper, the Kazakh people have been very interested in the events that took place in the Ottoman Empire.In each issue of the newspaper, the Kazakhs, who were informed about the news about the Ottoman Empire, closely followed the political events that took place in the Ottoman state.All issues published in the newspaper” external messages “ related to the Ottoman state were warmly received by the Kazakhs, considered the Turkish peopleas brothers and tried to provide maximum support to the Ottoman Empire, which was in a difficult situation.The section “external messages” inform about the Balkan wars, the coming to the head of state of young Turkish people , the wars between the Allied (Entente) States and the Ottoman Empire, The Grand National Assembly of Turkey.The main purpose of the article is to study the content of the history of the motherland as one of the ways to update and enrich the historical ties between Turkey and Kazakhstan. Key words: “Kazakh” newspaper, “Ak Zhol” newspaper, Ottoman Empire, Turkey, Turkestan, Balkan War, foreign publications, periodicals.